Generating Accessible Webpages from Models - Ordoñez-Briceño, Karla; Hilera, José R.; De-Marcos, Luis; Saraguro-Bravo, Rodrigo (Computers (Basel), 2025)
Despite significant efforts to promote web accessibility through the adoption of various standards and tools, the web remains inaccessible to many users. One of the main barriers is the limited knowledge of accessibility issues among website designers. This gap in expertise results in the development of websites that fail to meet accessibility standards, hindering access for people with diverse abilities and needs. In response to this challenge, this paper presents the ACG WebAcc prototype, which enables the automatic generation of accessible HTML code using a model-driven development (MDD) approach. The tool takes as input a Unified Modeling Language (UML) model, with a specific profile, and incorporates predefined Object Constraint Language (OCL) rules to ensure compliance with accessibility guidelines. By automating this process, ACG WebAcc reduces the need for extensive knowledge of accessibility standards, making it easier for designers to create accessible websites.